2008
DOI: 10.1089/hum.2007.123
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Bone Marrow Transduction by Gene Transfer with Allogeneic Umbilical Cord Blood Serum and Plasma: An Implication for Clinical Trials

Abstract: Low in vivo transduction efficiency and safety concerns have been hurdles for effective hematopoietic stem cell (HSC) gene therapy. Here, we investigate whether the safety and efficiency of retroviral gene transfer into HSCs can be improved by using human allogeneic umbilical cord blood (UCB)-derived supplements instead of fetal bovine serum (FBS). When CD34(+) cells were cultured ex vivo in UCB-derived serum (CBS) or plasma (CBP), comparable or higher maintenance of HSCs was observed than in FBS and serum-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…4A). These results revealed that cord blood serum contained abundant growth factors to maintain the proliferation potential of hPDMSCs over passages and to obtain large amounts of hPDMSCs ex vivo within a short time as others reported (15,25,36).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…4A). These results revealed that cord blood serum contained abundant growth factors to maintain the proliferation potential of hPDMSCs over passages and to obtain large amounts of hPDMSCs ex vivo within a short time as others reported (15,25,36).…”
Section: Discussionsupporting
confidence: 80%
“…So it is necessary to find a replacement for FBS in stem cell expansion throughout long-term culturing ex vivo. These include autologous or allogeneic human serum, human plasma, CBS, and human platelet derivatives (7,15,17,20,22,24,25,27,28,33,36). Of note, CBS is safe serum medium that carries no risk of xenogeneic antigen and has lower immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Human hematopoietic cells were similarly cultured ex vivo in serum-free substitution media containing 20% BIT as described. 25 Each culture was supplemented with growth factor cocktails containing 100 ng/mL human Flt3 ligand (R&D Systems), 100 ng/mL human stem cell factor (R&D Systems), and 20 ng/mL human interleukin-3, granulocyte colony-stimulating factor, and human interleukin-6 (R&D Systems).…”
Section: Ex Vivo Culturementioning
confidence: 99%
“…It is clear from previous research that CBP was shown to be richer for cytokines and growth factors compared to ABP and PRP (Ehrhart et al, 2018; Rhéaume et al, 2022). This approach has yielded notable successes in the treatment of neurodegenerative diseases, experimental autoimmune encephalomyelitis and hematopoietic stem cell gene therapy (Ehrhart et al, 2018; Kim et al, 2020; Moon et al, 2008). Despite these advancements, investigations into the impact of CBP derived from hUCB on POI remain notably scarce.…”
Section: Discussionmentioning
confidence: 99%